Robo-Robo Culture as Multiculturalism Education Based on Local Wisdom in the Kakap River Community in West Kalimantan - Khairuman; Ilham Samudra Sanur; Devi Wahyuni; Fitriani (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2023)
Multicultural education based on local wisdom can be used to solve various problems, with the aim of multicultural education based on local wisdom is to give young people an understanding of the values of local wisdom. Regarding the issues to be raised, namely how to instill multicultural values based on Robo-robo local wisdom for the Sungai Kakap community in West Kalimantan. The purpose of this study is to describe how to instill multicultural values based on Robo-robo local wisdom for the Sungai Kakap community and its conservation efforts, this aims to create citizens who have multicultural citizenship awareness. The research method used is descriptive with a qualitative approach. The results of the study show that multicultural values based on local wisdom in Robo-robo culture are able to lead society, especially students, to become human beings who care about their local culture. Apart from that, community leaders and the local government are also trying to preserve this culture, because traditional values in Robo-Robo culture are consultants of Islamic values, because Islam is the religious identity of the Malay people.